String Quartets by Soviet and Russian Composers in Memory of Shostakovich - Sokolvyak, Natalia L. (Music Scholarship / Problemy Muzykal’noj Nauki, 2014)
The article examines six string quartets by Soviet and Russian composers dedicated to the memory of Dmitri Shostakovich: Arno Babadjanyan’s Third String Quartet (1976), S. Tsintsadze’s Ninth String Quartet (1977), Yuri Falik’s Fourth String Quartet (1977), Alexei Nikolayev’s Third String Quartet (1981), Andrei Eshpai’s “Concordia discordans” String Quartet (1991) and Roman Ledenyov’s String Quartet “Contrasts” (2000). The author introduces the reader to the essential domain of memorial music of the last quarter of the 20th century – string quartets in memory of Dmitri Shostakovich, including the unpublished ones. The genre of the string quartet is presented as one of the predominant bearers of the tradition of the musical epitaph in Russian art. The influence of Shostakovich’s string quartet writing on the traits of the styles of the works dedicated to his memory is traced. The individual features of the composers’ conceptions of their memorial works, in which a dialogue of styles is combined with artistic traits characteristic for memorial music, are marked out. Keywords: Dmitri Shostakovich, memorial music, string quartet, poly-stylistics, dialogue of styles